Analisis Kelayakan Bisnis Produk Probiotik Ditinjau Dari Aspek Pasar Dan Pemasaran, Aspek Teknis, Dan Keuangan - Ahmad Zamakhsyari Sidiq; Iwan Kurniawan; Aris Muhammad Firdaus (LPPM Sekolah Tinggi Teknologi Cipasung, 2023)
Probiotics are a supplement for fish, in Kampung Tanjung, which is in Ciawang Village. There are tilapia fish farmers and some of these fish farmers have not used probiotics for tilapia, tilapia that die is caused by disease, one way to prevent disease is by administering probiotics. The purpose of this study was to determine the business feasibility analysis of probiotic products in terms of market and marketing aspects, technical aspects, and financial aspects. In order to reveal the problem in depth and thoroughly, a qualitative approach was carried out using observation techniques with the problem under study and a quantitative approach. Business feasibility analysis to take into account business feasibility before implementation, seen from market and marketing aspects using several analyzes such as STP analysis, SWOT analysis and 4P analysis. Technical aspects include tools and materials, and production processes. Financial aspects such as calculating the payback period formula, net present value, internal rate off return, and profitability index. The results of the analysis show that this probiotic product research is feasible to implement with a PI value of 1.2.